Biotechnological wood modification with selective white-rot fungi and its molecular mechanisms - Fackler, Karin (Array, 2007)
Microbial mechanisms of lignin degradation may be utilised for solid-state fermentations other than biopulping, during which the selective conversion of lignin is required. The current paper reviews current work into selective lignin conversion, with emphasis on the contributions made by our research group, which consists of researchers from five different laboratories. Three of them cooperate within Wood K plus. The recent research of this group has focussed on fermentations utilising the unique metabolism of selective white-rot fungi to modify wood surfaces during relatively short fermentation times of less than one week and on research into the molecular mechanisms causing these modifications. Lignin degradation by selective fungi (e.g. Ceriporiopsis subvermispora and species of the genus Phlebia) on the wood surfaces was significant after three days. After seven days the overall lignin content of spruce wood shavings was reduced by more than 3.5 %. Lignin loss was accompanied by an increase of extractable substances.